2001
DOI: 10.1177/00027640121957006
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Predictors of Daily Substance Use among Homeless Women of Different Ethnicities

Abstract: The objective of this study was to describe associations between childhood factors and adult daily substance use profiles among homeless women and to identify independent predictors of daily substance use for the overall sample and for ethnic/acculturation subgroups. Structured surveys were administered to 1,331 homeless women in Los Angeles who were either daily drug and alcohol users for the past 6 months or nondaily substance users. Physical abuse and parental drug abuse predicted daily drug use in the whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
4
22
0
3
Order By: Relevance
“…Similarly, Cuskey and Wathey (1982) found that more than 30% of addicts had been victims of childhood sexual abuse and/or had been physically abused. Similar patterns have been noted among alcoholics (Gomberg and Nirenberg, 1993), homeless males who use illicit drugs (Kim, 2004), female adolescent homeless runaways (Chen, Tyler, Whitbeck, and Hoyt, 2004), and female substance users (Nyamathi, Longshore, Keenan, Lesser, and Leake, 2001;Sterk, 1999). Likewise, Hartwell (2003) used a life history approach in following 31 homeless males in Connecticut and discovered that many had been the victims of neglect and abuse as children as well.…”
Section: Dietzsupporting
confidence: 61%
“…Similarly, Cuskey and Wathey (1982) found that more than 30% of addicts had been victims of childhood sexual abuse and/or had been physically abused. Similar patterns have been noted among alcoholics (Gomberg and Nirenberg, 1993), homeless males who use illicit drugs (Kim, 2004), female adolescent homeless runaways (Chen, Tyler, Whitbeck, and Hoyt, 2004), and female substance users (Nyamathi, Longshore, Keenan, Lesser, and Leake, 2001;Sterk, 1999). Likewise, Hartwell (2003) used a life history approach in following 31 homeless males in Connecticut and discovered that many had been the victims of neglect and abuse as children as well.…”
Section: Dietzsupporting
confidence: 61%
“…Similarly, Cuskey and Wathey (1982) found that more than 30% of addicts had been victims of childhood sexual abuse and/or had been physically abused. Similar patterns have been noted among alcoholics (Gomberg & Nirenberg, 1993), homeless males who use illicit drugs (Kim, 2004), female adolescent homeless runaways (Chen, Tyler, Whitbeck, & Hoyt, 2004), and female substance abusers (Nyamathi, Longshore, Keenan, Lesser, & Leake, 2001;Sterk, 1999). Likewise, Hartwell (2003) used a life history approach in following 31 homeless males in Connecticut and discovered that many had been the victims of neglect and abuse as children as well.…”
Section: Predictors Of Substance Misusesupporting
confidence: 54%
“…Substance use combined with homelessness can further be associated with other issues, such as a higher propensity to be victimized (Kushel, Evans, Perry, Robertson, & Moss, 2003). Interestingly, some researchers have noted a relationship between childhood victimization and substance misuse among the homeless (Nyamathi et al, 2001). Clearly, these studies, although they often relied upon small, geographically isolated samples, suggest that there may be an important relationship between victimization and substance abuse, particularly among the homeless.…”
Section: Predictors Of Substance Misusementioning
confidence: 99%
“…Além disso, crianças expostas à violência doméstica são mais propensas a apresentar problemas de saúde, incluindo ansiedade, depressão e violência com seus pares (Pournaghash-Tehrani & Feizabadi, 2009), delinquên-cia (Pastorelli;Steca;Gerbino & Vecchio, 2001), ideação suicida (Lai & Mcbride-Chang, 2001), dependência química (Nyamathi, Longshore, Keenan, Lesser & Leake, 2001) e repetição dos maus-tratos sofridos em seus filhos (De Antoni et al, 2007;Falcke, 2006;Mendlowicz & Figueira, 2007;Wareham et al, 2009). A violência familiar ocorre em um ciclo transmitido de geração para geração, sendo fundamental a compreensão deste processo.…”
Section: Violência No Contexto Familiarunclassified